La leadership politica in Italia alla luce della tradizione comica nazionale - Pozzato, Maria Pia (Incontri. Rivista europea di studi italiani, 2014)
Political leadership in Italy in the light of the national comical tradition This essay deals with humour and satire in politics. The issue of humour is contextualized within a wider cultural phenomenon called ‘show civilisation’ or ‘schermopolis’, i.e. the pervasiveness of screens in our everyday life. In doing so I will consider the role of new media and social networks in fostering the use of humour in political discourse. Next I will try to find a new framework for forms of popularity in politics by adapting to the current conjuncture the definitions given by Eric Landowsky at the end of the 1980s. Nowadays the politician-vedette is indeed the most popular form within the show civilisation phenomenon mentioned above. I will demonstrate that some Italian versions of this figure seem inspired by a rich Italian Comedy tradition. Finally, I will propose a number of hypotheses about the ways in which leaders obtain electoral consensus, for example through physical attractiveness, sympathy, and their ability to amuse people. In this perspective, a leader who is good for a laugh seems automatically a good leader.